Acute ethanol exposure inhibits silencing of cerebellar Golgi cell firing induced by granule cell axon input - Botta, Paolo; Zucca, Aya; Valenzuela, Carlos F. (Frontiers in Integrative Neuroscience, 2014)
Golgi cells (GoCs) are specialized interneurons that provide inhibitory input to granule cells in the cerebellar cortex. GoCs are pacemaker neurons that spontaneously fire action potentials, triggering spontaneous inhibitory postsynaptic currents in granule cells and also contributing to the generation tonic GABAA receptor-mediated currents in granule cells. In turn, granule cell axons provide feedback glutamatergic input to GoCs. It has been shown that high frequency stimulation of granule cell axons induces a transient pause in GoC firing in a type 2-metabotropic glutamate receptor (mGluR2)-dependent manner. Here, we investigated the effect ethanol on the pause of GoC firing induced by high frequency stimulation of granule cell axons. GoC electrophysiological recordings were performed in parasagittal cerebellar vermis slices from postnatal day 23 to 26 rats. Loose-patch cell-attached recordings revealed that ethanol (40 mM) reversibly decreases the pause duration. An antagonist of mGluR2 reduced the pause duration but did not affect the effect of ethanol. Whole-cell voltage-clamp recordings showed that currents evoked by an mGluR2 agonist were not significantly affected by ethanol. Perforated-patch experiments in which hyperpolarizing and depolarizing currents were injected into GoCs demonstrated that there is an inverse relationship between spontaneous firing and pause duration. Slight inhibition of the Na+/K+ pump mimicked the effect of ethanol on pause duration. In conclusion, ethanol reduces the granule cell axon-mediated feedback mechanism by reducing the input responsiveness of GoCs. This would result in a transient increase of GABAA receptor-mediated inhibition of granule cells, limiting information flow at the input stage of the cerebellar cortex.